Analisis Simpang Bersinyal Pada Simpang 4 Jl. Siliwangi Kota Tasikmalaya - Sholahudin, Farhan; Hendardi, Agi Rivi (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2020)
Transportation problem is one of the problems that is faced in Tasikmalaya City especially at the intersection. Congestion problems and traffic conflicts often occur at a signal especially in intersection on Siliwangi road Tasikmalaya. One of the efforts made to reduce traffic conflicts and optimize the performance of the junction is by setting up the junction and optimizing the Simpang. The purpose of this research is to know the performance of intersection on Siliwangi road Tasikmalaya and provide recommendations for precise handling, as well as analyzing the traffic conflicts that occurred in the junction. The method used in the performance analysis of the junction signal is to use the calculations in the PKJI 2014, while for analysis of traffic conflicts used to determine the severity of the conflict at the intersection on Siliwangi road Tasikmalaya is using the method Traffic Conflict Technique (TCT). After analysis, the performance in the intersection on Siliwangi road Tasikmalaya Tasikmalaya has approached the critical number of the degree of saturation (DS) of 0.7 with level D. In addition to these problems, there is a traffic conflict crossing as many as 230 events (55%), merging as many as 145 events (35%) and diverging as many as 41 occurrences (10%). With the handling and recommendation of phase setting and cycle time setting, it is proven to suppress and minimize the decline of junction performance level to C level with the value of saturation of 0.58. This will also impact the reduction in the amount of traffic conflicts that occur.Keyword : intersection, traffic conflict, PKJI 2014, phase, cycle time